THE IMPACTS OF PHYSICAL ACTIVITY ON MENTAL HEALTH IN PATIENTS WITH BURNOUT SYNDROME: A SYSTEMATIC REVIEW - Silva, Ana Beatriz Carvalho; Cursino, Ana Clara do Nascimento; Cursino, Gabriely Cristino; Camargo, Marcella Faria; Reis, Maria Luiza Martins dos; Lima, Lucas Mendes de; Santos, Thalita Pains Pamplona dos; Silva, Bruno Henrique da; Filho, Francisco Ronaldo Caliman; Lago, Heloiza Dias Lopes; et al. (CIPEEX, 2025)
Through a systematic review of the scientific literature, we analyze that physical activity has a notable influence on Burnout Syndrome, improving the individual’s well-being and promoting health and a better quality of life. Four articles available in the PubMed and SciELO databases were analyzed, using instruments such as the Maslach Burnout Inventory and the SF-36. The objective of the study was to capture the impacts of physical activity on mental health in patients affected by Burnout Syndrome. The results of the review point to a positive association between physical exercise and improved quality of life and health perception in these individuals.